1996
DOI: 10.1111/j.1600-9657.1996.tb00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulp exposure after stepwise versus direct complete excavation of deep carious lesions in young posterior permanent teeth

Abstract: The aim was to assess the prevalence of pulp exposure after stepwise versus direct complete excavation of permanent posterior teeth with deep carious lesions. The material, representing 116 patients aged 6-16 yrs (mean = 10.2 yrs), consisted of 127 teeth with radiographs revealing carious lesions to such a depth that pulp exposure could be expected if direct complete excavation was performed. Teeth with clinical symptoms, other than transient pain shortly before treatment, were not accepted. The teeth were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
147
1
39

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(194 citation statements)
references
References 12 publications
7
147
1
39
Order By: Relevance
“…In conventional treatment of deep lesions of caries, 40% of treated teeth had pulpal exposures compared to 17.5% with the stepwise approach. 4 A number of methods have been explored to assess the remaining dentine thickness…”
Section: Introductionmentioning
confidence: 99%
“…In conventional treatment of deep lesions of caries, 40% of treated teeth had pulpal exposures compared to 17.5% with the stepwise approach. 4 A number of methods have been explored to assess the remaining dentine thickness…”
Section: Introductionmentioning
confidence: 99%
“…Those who advocate for a longer waiting period (six months or longer) believe that this induces more tertiary dentin and thus reduces the risk of pulp exposure 38 . In their clinical study, Leksel et al 39 found no differences in exposure frequency between a group of lesions reopened after two months and another reopened after six months. The success of Stepwise excavation technique depends on the sealing: follow-up is essential.…”
Section: Discussionmentioning
confidence: 99%
“…5 Contudo, a grande desvantagem desta técnica é o risco de exposição pulpar durante o tratamento em cavidades profundas. 3 Devido ao risco elevado de exposição pulpar durante a RTTC 3 , houve a busca por tratamentos mais conservadores, sendo atualmente discutida a RPTC, com intuito de diminuir e prevenir a exposição pulpar, [6][7][8][9] suportados pelo conhecimento de que a RTTC não é necessariamente um indicador para o sucesso do tratamento das lesões cariosas. 4 Com o advento da Odontologia conservadora, propõe-se a preservação de uma camada da dentina desmineralizada sobre a polpa e a aplicação de um material forrador para induzir a formação de dentina terciária, selando a cavidade temporariamente, antes de realizar a restauração definitiva no dente.…”
Section: Partial Caries Removal In Permanent Teeth: An Integrative Reunclassified
“…7 O selamento da cavidade com materiais restauradores sobre a dentina cariada é capaz de estacionar a progressão da cárie por pelo menos 10 anos, indicando a não necessidade da remoção completa para a obtenção de sucesso clínico. 1 Além disso, o correto selamento da dentina cariada diminui significativamente a microbiota sobrevivente, 9 aumenta a dureza e reorganização da dentina, independente do material forrador utilizado. 7 Duas linhas têm sido bastante investigadas: a RPTC em dois passos ou stepwise excavation e a RPTC em sessão única, considerada conservadora.…”
Section: Partial Caries Removal In Permanent Teeth: An Integrative Reunclassified